Fishers' Perceived Objectives of Community-Based Coastal Resource Management in the Kei Islands, Indonesia - Hoshino, Eriko; van Putten, Elizabeth I.; Girsang, Wardis; Resosudarmo, Budy P.; Yamazaki, Satoshi (Frontiers in Marine Science, 2017)
Community-based resource management is a key approach to achieve successful small-scale fisheries and marine conservation. Many local management initiatives worldwide have been successfully managing aquatic resources and livelihoods of communities depending on them. Community-based management is particularly prevalent in small tropical islands where communities are frequently heavily dependent on coral reef ecosystems and small-scale reef fisheries for their livelihoods. Community-based management is, however, not always a panacea since there are inherit trade-offs among multiple objectives which are sometimes accentuated by community heterogeneity. It is well recognized that perceived and real evidence of community benefits are key to attributing success to local community-based management. However, broader understanding of community-based management objectives and how fishers’ perceived personal objectives and characteristics affect management outcomes remains limited. We apply a non-linear Principle Component Analysis (PCA) to explore variations in personally held community-based management objectives, based on local surveys for fishing communities in the Kei Islands in Indonesia. We then examine whether these variations also explain their perceptions of environmental and economic outcomes that are achieved by this management systems. In this study important differences are found in the perceptions fishers have of the relative importance of different community management objectives. The value people attribute to aspects of community management can be related to their socio-demographic characteristics and experienced fishers tend to focus more on environmental objectives. Given that strong links were found between community management outcomes and terrestrially based activities there is an opportunity to link in the terrestrial and coastal systems management and achieve multiple objective outcomes.